2023
DOI: 10.1088/1742-6596/2423/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

PUFJ (PolyUrethane Flexible Joints) as an innovative polyurethane system for structural and non-structural bonding of timber elements

Abstract: PolyUrethane Flexible Joints (PUFJ) as an innovative adhesive system has been developed by a team of researchers from the Cracow University of Technology (CUT) for several years. Initially, the research focused mainly on joining masonry and reinforced concrete elements. Due to environmental concerns and climate changes, further advancement of the PUFJ system was focused on the technology development based on connecting natural materials such as wood and wood-based materials. In 2019, the cooperation of the CUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…More advanced properties of the presented polyurethanes can be found in [34], where mechanical characterizations such as the storage moduli, obtained from DMA tests, are presented. More details concerning material properties of the considered polyurethanes can be found in [35].…”
Section: Flexible Polyurethanesmentioning
confidence: 99%
“…More advanced properties of the presented polyurethanes can be found in [34], where mechanical characterizations such as the storage moduli, obtained from DMA tests, are presented. More details concerning material properties of the considered polyurethanes can be found in [35].…”
Section: Flexible Polyurethanesmentioning
confidence: 99%
“…This flexibility helps to reduce the stress concentration at the joint interface and improve the overall performance of the structure. In addition, studies have found that polyurethane joints have greater shear strength, elastic stiffness, and strength degradation capability than mechanical fasteners commonly used in wood buildings [35][36][37]. Considering the advantages of polyurethane joints in terms of thermal stability and mechanical properties, they can also be a viable solution for post-fire interventions aimed at restoring the structural integrity of a wooden structure.…”
Section: Introductionmentioning
confidence: 99%